Professionals' perception of intimate partner violence in young people: a qualitative study in northern Spain - Amaia Maquibar; Carmen Vives-Cases; Anna-Karin Hurtig; Isabel Goicolea (BMC, 2017)
Abstract Background Intimate partner violence (IPV) is a public health problem with devastating effects on young women's health. These negative effects increase when the exposure to IPV lasts for a long time and exposure at an early age increases the risk of adult IPV. Despite efforts made in the last few decades, data show little progress has been made towards its reduction. Thus, the aim of the study reported here is to explore professionals' perceptions regarding intimate partner violence (IPV) among young people, focusing on the characteristics of the phenomenon and their perceptions about existing programmes and campaigns aimed at addressing it. Methods Twelve professionals from education, health and municipal social services were interviewed. All but one of the interviews were recorded and transcribed verbatim. Data were analysed according to the methodology of inductive thematic analysis, with the support of Atlas.ti software. The transcripts were read several times and coded line by line. Afterwards, codes were grouped into themes. The developed themes were refined into two phases with the participation of all the authors. Results From the analysis, the following three themes were identified: "A false sense of gender equity", "IPV among young people: subtle, daily and normalized", and "Mass media campaigns do not fit young people's needs". According to the participants, psychological abuse in the form of controlling behaviour by their partners is the most common type of IPV young women are exposed to, although exposure to other types of IPV was also acknowledged. This violence was described as something subtle, daily and normalized and, consequently, not something that is easy to recognize for the girls that are exposed to it, nor for adults working with young people. Conclusions The study participants showed good knowledge of the characteristics IPV has among young people. This knowledge was reflected in locally implemented IPV prevention projects, which they considered successful in addressing young people's needs. However, these interventions lacked formal evaluation, political support and continuation. The study participants did not believe that nationwide mass media campaigns realistically reflected the specific characteristics of IPV among young people. Thus, participants perceived these campaigns to be ineffective.